Perancangan Peningkatan Kinerja Green Supply Chain Management - Rahman Ramadhan, Diva; Cahyadi, Ujang; Chandrahadinata, Dody (Institut Teknologi Garut, 2025)
This research aims to determine the performance measurement of Green Supply Chain Management at PD SP Leather and to make improvements to the underperforming aspects. The stages of this research consist of two phases: measurement and improvement recommendations. The measurement is conducted using the Green Supply Chain Operations Reference (SCOR) method, assessing 6 business processes, namely Plan, Source, Make, Deliver, Return, and Enable. The improvement recommendations are made using the Analytical Hierarchy Process (AHP) method. The Green SCOR measurement results indicate that out of a total of 17 designed performance indicators, 6 of them are considered subpar. The prioritization of improvement is determined using the AHP method, resulting in 6 alternative improvement options. Subsequently, the impact of these alternatives on the other 11 indicators is assessed using the House Of Quality (HOQ).